2001
DOI: 10.1590/s1519-566x2001000300012
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Persistence of Two Formulations Containing Anticarsia gemmatalis Nuclear Polyhedrovirus (AgMNPV)

Abstract: estudadas. As formulações foram armazenadas em condições ambiente e expostas à radiação ultravioleta em condições de laboratório e à radiação solar em condições de campo. A formulação pó molhável (PM) foi preparada através da impregnação da suspensão de vírus e adjuvantes em inerte mineral (Caolin). A formulação óleo emulsionável (OE) foi preparada pela mistura da suspensão do patógeno com óleo + adjuvantes. Durante 20 meses, com intervalos de 120 dias, amostras das formulações e do vírus original eram adicion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The pH of the solution prior to the addition of NPV should be 5-7. Because OBs structures dissolve in alkaline substrates, it causes virulence to decrease in a short time (Batista et al 2001). Generally, cotton seed oil and corn oil were used in the oil-based baculovirus formulations (Shapiro et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pH of the solution prior to the addition of NPV should be 5-7. Because OBs structures dissolve in alkaline substrates, it causes virulence to decrease in a short time (Batista et al 2001). Generally, cotton seed oil and corn oil were used in the oil-based baculovirus formulations (Shapiro et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The prepared formulation initially (0. min) had a 98% mortality rate but decreased to 66% after 1 h of UV in laboratory conditions. Batista et al (2001) prepared 2 different formulations as emulsifiable oil (EO) and wettable powder (WP) of Anticarsia gemmatalis NPV. The crude virus, WP, and EO were exposed to UV in the laboratory for 5 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, several substances that were previously found to have photoprotective capacity, such as green tea, moringa, cacao, kaoline, iron oxide, charcoal, bentonite, benzopurpurine and benzimidazole [21,22,25,[30][31][32][33], were tested for the first time to determine their photoprotective activity to ChchNPV-TF1, and the joint effect virus-UV protectant on Chrysodeixis chalcites survival and plant photosynthetic activity. In our first assay, natural photoprotective substances were evaluated under laboratory conditions, and then two of the substances yielding the best results were tested in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Formulation of microbial cells has long been established for applications in the agricultural (Meyer, 2003), pharmaceutical (Tanaka et al, 1993;Frokjaer and Hovgaard, 2000) and industrial (Tanaka et al, 1993) sectors. The aims of formulating viable cells are to ensure that adequate cell viability is sustained to increase the efficacy of the cells and to facilitate the delivery and handling processes (Filho et al, 2001). This can be achieved by producing granular formulations, powder or dust formulations, microcapsules, or oilemulsion formulations (Brar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%